Holding on tight – NPM and the New Zealand performance improvement framework. Issue 2 (4th November 2019) - Allen, Barbara; Eppel, Elizabeth
Abstract: The New Zealand Government's Performance Improvement Framework (PIF) is aimed at public sector organisational improvement. The PIF exemplifies how the characteristics of new public management (NPM) challenge the evolution of performance systems attempting to go beyond performance management. The paper provides an empirical example of the operation of the PIF, using a theoretical frame derived from the literature. The analysis suggests that the PIF design does not yet mitigate the effects of gaming, synecdoche, and reputation‐protecting behaviour. The common graded ratings continue to hold the attention of those to whom the PIF is important, acting as a proxy for the whole performance of the organisation. This is a case study of how, despite promising adaptations, performance improvement efforts remain hampered by NPM limitations. Abstract : New Zealand Government's Performance Improvement Framework is aimed at public sector organisational improvement. This is a case study of how, despite adaptations, performance improvement efforts remain hampered by NPM limitations.